The Intriguing Regulators of Muscle Mass in Sarcopenia and Muscular Dystrophy - Sakuma, Kunihiro; Aoi, Wataru; Yamaguchi, Akihiko (Frontiers in Aging Neuroscience, 2014)
Recent advances in our understanding of the biology of muscle have led to new interest in the pharmacological treatment of muscle wasting. Loss of muscle mass and increased intramuscular fibrosis occur in both sarcopenia and muscular dystrophy. Several regulators (mTOR, serum response factor, atrogin-1, myostatin, etc) seem to modulate protein synthesis and degradation or transcription of muscle-specific genes during both sarcopenia and muscular dystrophy. This review provides an overview of the adaptive changes in several regulators of muscle mass in both sarcopenia and muscular dystrophy.